Virtual environment systems for a 3D perception research of the ski course - Aleshin, V.; Klimenko, S.; Klimenko, A.; Bobkov, A.; Novgorodtsev, D. (Abstractband der 6. Internationalen Konferenz Wissenschaft und Skisport. 14.-19. Dezember 2013, St. Christoph am Arlberg, Österreich, 2013)
Specifics of athlete 3D perception of ski course are of interest from both practical and theoretical points of view. The rapid progress of virtual environment technology and, in particular, computer vision makes it interesting to use these technologies for solving such issues. In 1967, the role of eye movement in visual perception was experimentally investigated for the first time (Yarbus, 1967). We continued the research (Aleshin et al., 2012) of the sportsman`s perception of ski course using different types of VE systems and tracking systems.